Pancasila sebagai Paradigma Etis bagi Transformasi Digital Pendidikan Indonesia - Ahmad Muhammad Mustain Nasoha; Jihan Putri Azh-zahra; Ria Nuraini; Sindy Amellya Sinta Dewi (Aktivisme: Jurnal Ilmu Pendidikan, Politik dan Sosial Indonesia, 2025)
The digital transformation of education in Indonesia presents both strategic opportunities and significant ethical challenges. On the one hand, technological innovation expands access, effectiveness, and quality of learning; on the other hand, it risks creating social disparities, the commercialization of education, and the reduction of human values. In this context, Pancasila is considered relevant as an ethical paradigm that guides the direction of digital transformation to remain grounded in humanity, social justice, and sustainability. This study aims to analyze Pancasila as an ethical framework for directing the development of educational technology in Indonesia. The method employed is a literature review with a qualitative-descriptive approach, drawing on philosophical sources, educational policy documents, and practices of digital technology implementation at various educational levels. The analysis reveals that the values of Pancasila, particularly the second and fifth principles, can serve as normative foundations for shaping policies, design, and practices of educational technology that are humanistic, inclusive, and equitable. The study concludes that integrating the Pancasila paradigm is not only ideologically essential but also strategically significant in ensuring that the digital transformation of education in Indonesia aligns with national objectives and human dignity.